Role of kynurenine on platelet's function and beyond - AL-SHIBLAWI, NADHIM KAMIL (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2020)
Kynurenine is a metabolite of the amino acid tryptophan by the action of the tryptophan dioxygenase enzyme in the liver and the ubiquitous indolamine dioxygenase enzyme in other tissues. Although it has been shown that kynurenine participates in different processes involving the central nervous-, immune- and cardiovascular- systems, its effect on platelet function has not been yet investigated. In this study, it is shown for the first time that kynurenine inhibits collagen-, adenosine diphosphate-, thromboxane- and arachidonic acid- induced platelet aggregation. The mechanism by which kynurenine modulates platelet function involves the activation of the adenylyl cyclase (AC) enzyme and of the reduced and oxidized heme forms of the soluble guanylyl cyclase (sGC) enzyme. Activation of those enzymes leads to an increase of cyclic guanosine monophosphate (cGMP) and cyclic adenosine monophosphate (cAMP) respectively. Kynurenine phosphorylates the vasodilator stimulated phosphoprotein (VASP) by cAMP- and cGMP-dependent protein kinases. VASP participates in cytoskeleton redistribution during platelet shape change and in GPIIb/IIIa activation. Kynurenine may represent a natural endothelial derived inhibitor of platelet aggregation that can activate both, adenylyl cyclase and guanylyl cyclase. Kynurenine may activate the soluble guanylyl cyclase enzyme when the enzyme is refractory to NO and therefore may represent a physiological back up system for NO and a new therapeutic approach in pathological conditions where oxidative stress inactivates platelet response to NO. In fact, studying the binding site of kynurenine to both forms of soluble guanylyl cyclase may open the door for the development of novel therapeutic compounds that could activate both forms of the enzyme. Having found that kynurenine have the ability to inhibit platelet aggregation induced by collagen, ADP, the thromboxane analogue U46619 and arachidonic acid. The effect of kynurenine on platelet function resulted to be cGMP and cAMP dependent, meaning that the effect of this tryptophan metabolite can be linked with most of the major pathways involved in platelet aggregation. Those findings, together with the already known participation of kynurenine in cancer biology, led us to investigate its potential effect on TCIPA. TCIPA refers to the ability of cancer cells to aggregate platelets and constitutes a crucial step during cancer cell invasion, angiogenesis and during the development of metastatic foci. It has been shown that tumour cell lines differ in their capability to induce platelet aggregation and that the mechanism by which TCIPA takes place can also vary from one cell line to another. Kynurenine (100-500 ?M) significantly inhibited TCIPA induced by A549, Hela, HT-29, SW-480 and HCC-1954 cells. However, the amount of kynurenine produced by the different cell lines in vitro did not justify and did not correlate with the differences in their capability to induce platelet aggregation. Pharmacological modulation of kynurenine generation by the induction and/or inhibition of the indoleamine 2,3-di-oxygenase (IDO) enzyme in HCC-1954 and A549 cells (the most and the least potent cell line inducing TCIPA) did not modify their potency towards TCIPA indicating that, at the induced concentrations, kynurenine was not able to inhibit this interaction. A new approach preparing platelets suspension using conditioned media to look at platelet function was also investigated. The ability of platelets re-suspended in conditioned media from A549 cells, to aggregate in the presence of collagen, HCC-1954 and A549 cells was found to be significantly reduced when compared to platelets re-suspended in fresh media. On the other hand, when platelets suspensions were prepared in HCC-1954 conditioned media, platelets aggregated spontaneously in the absence of any stimuli. This research demonstrates, for the first time, that 1) kynurenine is able to inhibit platelet aggregation induced by a wide range of cancer cell lines although at higher concentrations than the ones produced by the cells in vitro conditions 2) conditioned media from tumour cell lines that have the ability to aggregate platelets, and therefore to induce TCIPA, can exert opposite effects on platelet function. This novel approach has the potential to provide a better insight for looking at the effect of cell derived mediators that could inhibit or induce platelet aggregation within the tumour microenvironment and deserves more attention and to be further investigated.
APPROVED
Keywords: Kynurenine; platelet aggregation; tumor cell induced platelet aggregation; conditioned media and TCIPA; kynurenine mechanism of action; TCIPA